2019
DOI: 10.1175/mwr-d-18-0345.1
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Eyewall Replacement Cycles in Hurricane Frances (2004)

Abstract: Hurricane Frances (2004) represented an unusual event that produced three consecutive overlapping eyewall replacement cycles (ERCs). Their evolution followed some aspects of the typical ERC. The strong primary eyewalls contracted and outward-sloping secondary eyewalls formed near 3 times the radius of maximum winds. Over time these secondary eyewalls shifted inward, became more upright, and replaced the primary eyewalls. In other aspects, however, the ERCs in Hurricane Frances differed from previously describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Because tropical cyclone (TC) intensity is influenced by multiple factors spanning different spatiotemporal scales (Marks et al 1998, Rogers et al 2006Dougherty et al 2018), our investigation is based on four aspects: 1) large-scale atmospheric environment, e.g. VWS and relative humidity (RH) (De Maria et al 2005;Knaff et al 2005;2018; Kaplan et al 2010;; 2) large-scale pre-TC ocean environment and local-scale, during-TC air-sea interactions, e.g., pre-TC Sea Surface Temperature (SST), pre-TC Ocean Heat Content (OHC), TC's self-induced ocean cooling effect (during-TC), and the during-TC air-sea fluxes (Shay et al 2000;Cione and Uhlhorn 2003;Lin et al 2008Lin et al , 2013Goni et al 2009;Cione 2015;Jaimes et al 2015;Tsuboki et al 2015;Zhang et al 2017;Chih and Wu 2020); 3) vortex-scale properties, e.g., storm size, translation speed (Uh), and ERCs (Chavas and Emanuel 2010;Chan and Chan 2012;Knaff et al 2016;Molinari et al 2019;Shen et al 2021); and 4) convective-scale features, e.g., radial location of deep convection (Rogers 2010;Rogers et al 2013Rogers et al , 2015Rogers et al , 2016Miyamoto and Takemi 2015;Kanada et al 2017;Hu and Wu 2020;Peng and Wu 2020). For observations, atmospheric environmental data is from the US National Centers for Environmental Prediction Climate Forecast System Reanalysis (NCEP CFSR-V2, 6-hrly/1∘data).…”
Section: Methodsmentioning
confidence: 99%
“…Because tropical cyclone (TC) intensity is influenced by multiple factors spanning different spatiotemporal scales (Marks et al 1998, Rogers et al 2006Dougherty et al 2018), our investigation is based on four aspects: 1) large-scale atmospheric environment, e.g. VWS and relative humidity (RH) (De Maria et al 2005;Knaff et al 2005;2018; Kaplan et al 2010;; 2) large-scale pre-TC ocean environment and local-scale, during-TC air-sea interactions, e.g., pre-TC Sea Surface Temperature (SST), pre-TC Ocean Heat Content (OHC), TC's self-induced ocean cooling effect (during-TC), and the during-TC air-sea fluxes (Shay et al 2000;Cione and Uhlhorn 2003;Lin et al 2008Lin et al , 2013Goni et al 2009;Cione 2015;Jaimes et al 2015;Tsuboki et al 2015;Zhang et al 2017;Chih and Wu 2020); 3) vortex-scale properties, e.g., storm size, translation speed (Uh), and ERCs (Chavas and Emanuel 2010;Chan and Chan 2012;Knaff et al 2016;Molinari et al 2019;Shen et al 2021); and 4) convective-scale features, e.g., radial location of deep convection (Rogers 2010;Rogers et al 2013Rogers et al , 2015Rogers et al , 2016Miyamoto and Takemi 2015;Kanada et al 2017;Hu and Wu 2020;Peng and Wu 2020). For observations, atmospheric environmental data is from the US National Centers for Environmental Prediction Climate Forecast System Reanalysis (NCEP CFSR-V2, 6-hrly/1∘data).…”
Section: Methodsmentioning
confidence: 99%
“…During 6hr‐long precipitation pulse events, the precipitation signal only translates 300 km outward, but the cloud top cooling signature propagates at least 500 km away. On the other hand, less than 20% (561) of the precipitation pulses occur in the absence of cold‐cloud pulse, which may be partially associated with the eyewall replacement cycles or rainband activity (Fischer et al., 2020; Molinari et al., 2019; Sitkowski et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…While TCs typically weaken during ERCs, recent work has found that in some cases the TC will fail to weaken as the ERC completes (Dougherty et al 2018), or even rapidly intensify (Fischer et al 2020). The variability of the temporal scales of ERCs has also been noted, as the duration of an ERC can range from less than 12 h to multiple days (Molinari et al 2019;Fischer et al 2020). Furthermore, the nature of TC convective asymmetries during ERCs has been assessed (Didlake et al 2017;Dougherty et al 2018;Didlake et al 2018;Fischer et al 2020).…”
Section: Secondary Eyewall Formation and Eyewall Replacement Cyclesmentioning
confidence: 99%